2022
DOI: 10.1111/jftr.12446
|View full text |Cite
|
Sign up to set email alerts
|

Progress and gaps: A systematic review of the family demographics and family subsystems represented in top family science journals 2008–2018

Abstract: Recent critiques suggest family science is operating on a narrow definition of family that privileges US/western-centric perspectives and White, heteronormative, and nuclear families. Understanding that self-assessment is key to scientific growth, this study systematically assessed the publication patterns of the top six family science journals across 10 years (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) along two dimensions: the sociodemographics (continent/country, ethnic-racial group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Additionally, multiple recent systematic review papers have highlighted a major lack of diversity in the samples used in family and relationship science. A review of studies focusing on family systems found that the majority of samples were comprised of White families from Western countries, and less than 3% of all coded studies focused on LGBTQ families (Perez-Brena et al, 2022). Similarly, a review of studies focusing on intimate relationships found that the samples used in these studies are largely composed of individuals and couples who are in their 20s and 30s, White, American, middle-class, college educated, and involved in a differentsex, same-race relationship (Williamson et al, 2022).…”
Section: Innovative Strategies For Increasing Sample Size and Diversi...mentioning
confidence: 99%
“…Additionally, multiple recent systematic review papers have highlighted a major lack of diversity in the samples used in family and relationship science. A review of studies focusing on family systems found that the majority of samples were comprised of White families from Western countries, and less than 3% of all coded studies focused on LGBTQ families (Perez-Brena et al, 2022). Similarly, a review of studies focusing on intimate relationships found that the samples used in these studies are largely composed of individuals and couples who are in their 20s and 30s, White, American, middle-class, college educated, and involved in a differentsex, same-race relationship (Williamson et al, 2022).…”
Section: Innovative Strategies For Increasing Sample Size and Diversi...mentioning
confidence: 99%
“…Despite their prevalence, variable relationships and family structures have remained consistently understudied and underaddressed in the empirical and clinical family literatures (Browning & van eeden-Moorefield, 2022; Ganong et al, 2015; Perez-Brena et al, 2022). Of 3,932 peer-reviewed articles published in top family science journals from 2008 to 2019, only 10% of articles focused on anything other than biological parent–child or intimate couple (predominately different-sex marital couple) relationships (Perez-Brena et al, 2022).…”
Section: The Study Of Structurally Diverse Families: Contemporary Dem...mentioning
confidence: 99%
“…Despite their prevalence, variable relationships and family structures have remained consistently understudied and underaddressed in the empirical and clinical family literatures (Browning & van eeden-Moorefield, 2022; Ganong et al, 2015; Perez-Brena et al, 2022). Of 3,932 peer-reviewed articles published in top family science journals from 2008 to 2019, only 10% of articles focused on anything other than biological parent–child or intimate couple (predominately different-sex marital couple) relationships (Perez-Brena et al, 2022). When more diverse forms of family structures are studied, investigations are most frequently framed from a deficit-comparison approach in which diverse family forms are compared to nuclear families with a presumption that difficulties, challenges, or variations in individual experiences are the result of some failing of those alternative structures (or the individuals living in them; Ganong et al, 2015; Jensen & Sanner, 2021).…”
Section: The Study Of Structurally Diverse Families: Contemporary Dem...mentioning
confidence: 99%
“…Furthermore, of the studies reviewed, only 74 (10%) focused on traditionally underrepresented groups (e.g., those who are low income, sexual and gender minorities, and/or are not White; Williamson et al, 2022). Third, in a systematic review of six family science journals from 2008 to 2018, resulting in 3932 coded studies, 85% of the studies included North American and Western European samples (Perez‐Brena et al, 2022). Furthermore, within the US‐based studies, White samples made up more than half of all research, and less than 3% of all coded studies focused on LGBTQ families (Perez‐Brena et al, 2022).…”
Section: Relational Sacrifices and Well‐being: What Do We Know And Ho...mentioning
confidence: 99%